2019
DOI: 10.7126/cumudj.589413
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mineral Trioxide Aggregate, Endosequence Root Repair Material, and Biodentine Used for Repairing Root Perforations: A Systematic Review

Abstract: The root perforation, in spite of being taken as a challenging accident in root canal treatment, has to offer favorable results when exposed to appropriate therapeutic conduct and the usage of materials that have convenient properties. The aim of the current review is to collect all updated and available studies including imperative information concerning the use of Mineral trioxide aggregate, EndoSequence root repair material and Biodentine in the treatment of root perforation approaching some of the key prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Bioceramic sealers have recently gained attention in the field of endodontic since they can form anapatite layer, allowing intrafibrillar apatite deposition. 13,27 This promotes the formation of a tag-like structure which plugs along with the dentine bonding interface, thus, creating a strong mineral infiltration zone resulting in a better seal. 28 Although bioceramic sealers (EndoSeal MTA and BioRoot RCS)in the present study demonstrated excellent sealing ability which is in agreement with the other authors [29][30][31] , but several studies found that there is no significant difference when comparing the sealing ability of bioceramic sealers with resin and calcium hydroxide based sealers.…”
Section: Discussionmentioning
confidence: 99%
“…Bioceramic sealers have recently gained attention in the field of endodontic since they can form anapatite layer, allowing intrafibrillar apatite deposition. 13,27 This promotes the formation of a tag-like structure which plugs along with the dentine bonding interface, thus, creating a strong mineral infiltration zone resulting in a better seal. 28 Although bioceramic sealers (EndoSeal MTA and BioRoot RCS)in the present study demonstrated excellent sealing ability which is in agreement with the other authors [29][30][31] , but several studies found that there is no significant difference when comparing the sealing ability of bioceramic sealers with resin and calcium hydroxide based sealers.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Alghamdi and Aljahdali (2019, P.474) established that there is no unanimity in regards to the most suitable material that can be utilized for the treatment of root perforation [1]. Alghamdi and Aljahdali (2019, P.474) claim that some of the studies reviewed in their research revealed that the assessment of the sealing capacity of biodentine and MTA led to the declaration that no considerable differences were noticed between the two materials, with biodentine being preferred as an alternative to MTA [1]. Mangala (2020) concluded that MTA is better than bioentine in the primary teeth' pulpotomy [14].…”
Section: Author and Year Inclusion Criteria Findings [1] Addressed Mt...mentioning
confidence: 99%
“…Root perforation is any condition be it pathologic or accidental exposure that leads to direct communication between pulp cavity and periodontal tissues as a result of reabsorption, iatrogenic, or dental caries [1,2]. Root perforation is believed to be one of the most unprecedented accidents that happen during endocrine treatment subsequently several prominent clinicians and endodontic subspecialties see this condition as challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been found that it does not interact with root canal irrigants. The setting time of biodentin also makes it a suitable material for repair of furcal perforations [27] . Study by Mancino D et al, has shown that biodentine is a highly effective repair material even for old infected perforations with a success rate of 94% [28] .…”
Section: Perforation Repairmentioning
confidence: 99%